EFISIENSI PEMANFAATAN INPUT PRODUKSI USAHATANI PADI LADANG DI KECAMATAN BUNGKU UTARA KABUPATEN MOROWALI - Nilam Sari (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
This research aimed at finding out: (a) factors influencing the dryland paddy production at Bungku Utara Sub-district; and (b) the efficiency of the use of the production factors at the dryland paddy farming.  A multistage random sampling technique was applied to draw out samples for this research.  Firstly, the sample of villages was determined using a purposive sampling method. Three villages were then chosen as the location of the research.  They were village of Baturube, village of Kalombang and village of Womparigi.  Secondly, the sample of farmers involved was determined.  Since there were 230 farmers from those 3 villages,a simple random sampling method was used to draw 130 of them as the sample of the research subject.  The research findings showed that (a) the production factors of land size, urea fertilizer, SP36 fertilizer and KCl fertilizer have a significant influence on the dryland paddy production, while the other factors such as seed, pesticide and human labor have no significant influence; and (b) economically, the use of production factors such as land size, seed, urea, SP36, and KCl fertilizers, pesticide and human labor was sufficiently inefficient.